Pengaruh Pengetahuan Investasi, Motivasi, dan Uang Saku terhadap Minat Mahasiswa Berinvestasi di Pasar Modal Syariah dengan Risiko Investasi sebagai Variabel Intervening - Silvi Adiningtyas; Luqman Hakim (ITB AAS INDONESIA Surakarta, 2022)
Many factors influence student interest in investing, including knowledge about investment, motivation to invest, and pocket money. In addition to the benefits obtained from investment, it is also a reason for a student to invest. The purpose of this research was to know investment understanding effect, motivation, as well as pocket money, interested in investing on the Islamic capital market with investment risk as an intervening variable. The population in this study were students of the State University of Surabaya and the State Islamic University of Surabaya quota sampling technique is used in research. This research data collection uses primary data in the form of a question questionnaire that already has answer choices. Results obtained of this research is indicate that there is a direct influence between knowledge, motivation, and pocket money then interesting to lnvestment. Investment risk is an intervention variable between investment knowledge then pocket money on investment interest. Investment risk is not an intervention variable between motivation and investment interest.